(untitled) (Linguostylistic Studies, 2018)
More and more often dialectologists highlight the issues of text as the subject of their scientific studies, regarding it as a self-sufficient source of information that contains a complex and diverse arsenal of folk language units, all the elements of which are closely interconnected. Description of the phonetic specificities of local dialects in this research is based on the case study of the folklore texts recorded in the Ratno district of the Volyn region.The article deals with the detailed analysis of the reflection of ancient and positional variants of modern vowels, the peculiarities of the depalatalization of the consonants, differences in the frequency of some consonants usage and the consequences of the positional and irregular sound alterations. It has been revealed that only professionally recorded folk poetic texts provide linguists with reliable information and enable them to conduct a systemic study of the structural levels of the Ukrainian dialectal speech. This approach allows to single out two types of the folklore collections: the compilers of the first type philologically accurately reproduced the peculiarities of the folk speech, while the collection of the second type involves the texts which have undergone editorial amendments in the course of preparing them for publication and, therefore, lack the completeness and consistency of the material presentation. The article argues that achieving the compliance of oral folk art records with the requirements of a source, which ought to be quality-reliable and informative, can help to solve the problem of expediency of their involvement into the diverse dialectological research. It also alleviates the elaboration of the theoretical framework that still has not been authenticated in the field of Slavicity regarding the typology of the ethnopoetic texts and local dialects interconnections. Systemic application of the theoretical tools to oral poetic texts used in modern dialectological studies will contribute to verifying the heuristic potential of the folklore text as a specific source of linguistic information.